BIOLOGICAL ASPECTS OF FOURFINGER THREADFIN (Eleutheronema tetradactylum) IN MENDAHARA ILIR EAST TANJUNG JABUNG REGENCY JAMBI - Ester Restiana Endang Gelis; Rizky Janatul Magwa; Yoppie Wulanda; Lauura Hermala Yunita; Septy Heltria; Farhan Ramdhani (JURNAL PERIKANAN TROPIS, 2026)
The fourfinger threadfin (Eleutheronema tetradactylum) is an economically important but increasingly threatened species classified as Endangered on the IUCN Red List. This study examined biological aspects of E. tetradactylum in the waters of Mendahara Ilir, East Tanjung Jabung Regency, Jambi. The research focused on the length-weight relationship (LWR), condition factor (K), relative weight (Wr), and size-based fishing eligibility. A total of 340 specimens, consisting 161 males and 179 females, were collected using gill nets. The LWR equations revealed  W = 0.002444L3.3306 (R² = 0.9571) for males and W = 0.005523L3.1116 (R² = 0.9623) for females, indicating positive allometric growth in males and near-isometric growth in females. The t-test confirmed that both b values differed significantly from 3 (p < 0.001). The mean condition factor (K) was 2.83 ± 0.14 for males and 2.91 ± 0.07 for females, while the mean relative weight (Wr) was 101.46 for males and 100.98 for females, indicating good physiological condition and favourable habitat quality. However, analysis of fishing eligibility revealed that only 48.60% of female fish had reached the minimum catchable size (Lc = 40.0 cm), compared to 72.05% of males that exceeded their threshold (Lc = 29.0 cm). The high proportion of undersized female fish raises serious concerns about potential recruitment overfishing. These findings underscore the urgent need to implement for size-selective fishing regulations in Mendahara Ilir waters.